The Iraqi satellite channel marketing the Iraqi national identity during the protests: Research extracted from a doctoral thesis - Hussein Abed, Alaa; Fadel Zeidan, Nahed (ALBAHITH ALALAMI, 2022)
The escalating development of technology is one of the distinctive features of the communication environment in the field of sending and receiving satellite broadcasts of television channels in general and Iraqi satellite channels in particular, which contributed to the wide and rapid spread and reaching outside the drawn boundaries and bypassing even natural obstacles, and what is important in this is the communication content that these broadcasts Channels and its impact on the recipient due to the media, cultural, educational and entertainment content it provides, and in our research we will analyze the communication content of the Iraqi satellite channel by choosing one of its dialogue programs that coincided with the events of the legislative protests that started in Iraq on the first of October of 2019, and how they contributed to strengthening the Iraqi national identity By inculcating concepts and contents that the protesters interacted with, because they support the Iraqi national identity.